High-performance scientific computing : first JARA-HPC Symposium, JHPCS 2016, Aachen, Germany, October 4-5, 2016, revised selected papers /: first JARA-HPC Symposium, JHPCS 2016, Aachen, Germany, October 4-5, 2016, revised selected papers. (2017) - Unknown
No abstract available